Chemotherapy reduces PARP1 in cancers of the ovary: implications for future clinical trials involving PARP inhibitors - Marques, Maud (BMC Med, 2015)
BACKGROUND: PARP inhibitors have shown promising clinical results in cancer patients carrying BRCA1/2 mutations. Their clinical efficacy could logically be influenced by PARP1 protein levels in patient tumors. METHODS: We screened three cohorts of patients with ovarian cancer, totaling 313 samples, and evaluated PARP1 protein expression by immunohistochemistry with further validation by western blotting. RESULTS: We observed that up to 60 % of tumors showed little PARP1 protein expression. In serous ovarian tumors, comparing intratumoral PARP1 expression between chemo-naïve and post-chemotherapy patients revealed a decrease in intratumoral PARP1 following chemotherapy in all three cohorts (immunohistochemistry: p < 0.001, n = 239; western blot: p = 0.012, n = 74). The findings were further confirmed in a selection of matched samples from the same patients before and after chemotherapy. CONCLUSION: Our data suggest that patients should be screened for PARP1 expression prior to therapy with PARP inhibitors. Further, the observed reduction of intratumoral PARP1 post-chemotherapy suggests that treating chemo-naïve patients with PARP inhibitors prior to the administration of chemotherapy, or concurrently, might increase the responsiveness to PARP1 inhibition. Thus, a change in the timing of PARP inhibitor administration may be warranted for future clinical trials. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12916-015-0454-9) contains supplementary material, which is available to authorized users.